2022
DOI: 10.1101/2022.09.13.507744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diacammaants adjust liquid foraging strategies in response to biophysical constraints

Abstract: Ant foragers need to provide food to the rest of the colony, which often requires food transport over long distances. Foraging for liquid is especially challenging because it is difficult to transport and share. Many social insects store liquid food inside the crop to transport it to the nest, and then regurgitate this fluid to distribute it to nestmates through a behaviour called trophallaxis. Some ants instead transport fluids with a riskier behaviour—holding a drop of liquid between the mandibles through su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In the two early gains of trophallaxis ( Ectatomminae species lost worker reproductive potential rather late, about 40-25 Ma, and yet they still do not perform true trophallaxis. This indicates that there was either some form of critical period connected to ecological changes, or that these species may be transitioning to using trophallaxis, perhaps through mandibular pseudotrophallaxis 16,25 . In multiple other subfamilies, the species present in our dataset never evolved trophallaxis in accordance with our hypothesis (Leptanillinae, Apomyrminae, Proceratiinae, Amblyoponinae and Agroecomyrmecinae, Fig 2): sugary liquids were never integrated into the diet, workers lost full reproductive potential, and trophallaxis never evolved.…”
Section: Uncertainty Of Predicted Presence or Absence Of Trophallaxis...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the two early gains of trophallaxis ( Ectatomminae species lost worker reproductive potential rather late, about 40-25 Ma, and yet they still do not perform true trophallaxis. This indicates that there was either some form of critical period connected to ecological changes, or that these species may be transitioning to using trophallaxis, perhaps through mandibular pseudotrophallaxis 16,25 . In multiple other subfamilies, the species present in our dataset never evolved trophallaxis in accordance with our hypothesis (Leptanillinae, Apomyrminae, Proceratiinae, Amblyoponinae and Agroecomyrmecinae, Fig 2): sugary liquids were never integrated into the diet, workers lost full reproductive potential, and trophallaxis never evolved.…”
Section: Uncertainty Of Predicted Presence or Absence Of Trophallaxis...mentioning
confidence: 99%
“…A majority of ecosystem-dominating generalist ants perform a behavior called stomodeal trophallaxis, wherein adult workers regurgitate the contents of their crop to nestmates in a mouth-to-mouth interaction 14 , though it is not clear why these traits appear to co-vary. It has been suggested that trophallaxis behavior evolved to transport sugary liquids acquired through mutualisms with sapsuckers or with plants 15,16 . Species that use trophallaxis tend not to have a sting and tend to have sterile workers or workers that cannot be mated, suggesting that these traits might prohibit the evolution of trophallaxis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A longer waiting time between subsequent unloading interactions is experienced by honey bee foragers if the colony is satiated 52 ; among ants, receiving a particular type of food 53 and deprivation of required nutrients 54 leads to colony satiation. The viscosity of food source (sugar) impacts the number of trips and method through which sucrose solution is shared by nestmates in D. indicum 55 , 56 . D. indicum foragers are solitary scavengers that occasionally hunt for termites.…”
Section: Introductionmentioning
confidence: 99%
“…Data accessibility. All data and codes are available at: https://doi.org/ 10.5061/dryad.x95x69png [57].…”
mentioning
confidence: 99%